To find which of the following equations has (2, -1) as a solution, we just need to substitute the x and y values shown in the ordered pair into the equation, and if it simplifies into a true statement, then it will be a solution.
A) y = 2x - 1
-1 = 2(2) - 1
-1 = 4 -1
-1 = 3
Except, -1 ≠ 3, so the answer isn't A.
B) y = x + 3
-1 = 2 + 3
-1 = 5
Except, -1 ≠ 5, so the answer isn't B either.
C) y = x -3
-1 = 2-3
-1 = -1
-1 does equal -1, so the answer is C.
Just to be sure, we should make sure that answer D doesn't work either.
D) y = -2x + 1
-1 = -2(2) + 1
-1 = -4 + 1
-1 = -3
-1 doesn't equal -3, so D isn't the answer.
Therefore, the equation that has (2, -1) as a solution is C) y = x - 3.